Case study and Design for a Professional Education Curriculum (Trinity Journal of Management, IT & Media (TJMITM), 2011)
Today at the dawn of modem education era, we are  constantly facing new opportunities and challenges.  Professional education in particular faces a Herculean  challenge of bridging the gap between traditional  classroom lessons and changing industry scenario.  Consequently educators today are exploring alternative  pedagogy methodologies to capture student attention.  One such approach, Activity Based Learning, brings  together thinking, doing and learning to make education  an experience beyond mere memorizing. This paper  aims at illustrating successful case studies of ABL systems and design of similar activities for practical  implementation in a professional education curriculum.
Keywords: Professional Education; Herculean; methodologies